DINAMIKA PENGELOLAAN WILAYAH PESISIR DI KABUPATEN REMBANG - Kismartini, Kismartini (JURNAL ILMU SOSIAL, 2014)
Coastal zone management is complex, from the results of the research showed that many stakeholders involved in coastal management. Among them are from government agencies (Department of Marine and Fisheries, Bappeda, Department of Culture, Tourism and Sport, Department of Transportation, Office of Environment, DPRD), Private and Public sector. The key role is in the Department of Marine and Fisheries, while BAPPEDA have a very important role in the coordination between stakeholders. Efforts can be made to involve stakeholders better is through understanding the role of each stakeholder, and then optimize the role of coastal zone management in order to obtain effective and efficient.